Barriers and the limits of neodevelopmentalism: Lessons from Argentina's experience, 2003-2011 - Féliz, Mariano (2015)
In this paper we study the development of contradictions, barriers and limits in Argentina's new pos-neoliberal hegemonic project: neodevelopmentalism. In the following section we will briefly describe the constitution and basic foundations of this new process. We'll show how neodevelopmentalism has worked as an attempt by dominant fractions of capital to take advantage of the neoliberal legacy while at the same time attempting to surpass its limitations. Later on, we present the basic contractions and barriers of this new project as they manifest themselves as forms of class struggle. Finally, we'll discuss how neodevelopmentalism in Argentina manages the impact of the first crisis in world capitalism in the 21st century. Finally we present some conclusions.